Self-Esteem and Associated Factors among Medical Students of a Private Medical College in Koshi Province - Niroula, Aarju; Guragain , Parth; Agrawal , Hulas; Bhagat , Divya (Journal of College of Medical Sciences-Nepal, 2025)
Background: Self-esteem defined as an individual’s perception of self-worth, self-acceptance, and confidence, plays a crucial role in mental well-being. Medical students are particularly vulnerable to diminished self-esteem due to persistent academic demands, financial burdens and social stressors. World Health Organization has identified self-esteem as a significant public health concern among students. This study aims to assess the level of self-esteem among medical students at a private medical college in Koshi Province, Nepal, and its associated factors.Materials and methods: A descriptive cross-sectional study was carried out among medical students of a private medical college in Koshi Province from August 2024 to January 2025. Using a census method, 230 students were included in the study. The Rosenberg Self-Esteem Scale was utilized to evaluate the level of self-esteem. Data were collected through a structured questionnaire distributed via Google Forms through email. To assess the association between self-esteem and various factors, Chi-square test was applied, with statistical significance set at a p-value of less than 0.05.Results: This study included a total of 230 participants, among which 27% students showed low self-esteem. 66% had normal self-esteem and 7% had high self-esteem. Female participants had significantly low self-esteem, whereas Age, gender, schooling, and level of education were not significant.Conclusion: Most medical students had normal self-esteem, though a considerable number exhibited low self-esteem. Programs aimed at enhancing self-esteem should be implemented to support medical students in developing confidence and effectiveness in their future medical practice.